Let's make Pulvigera great again: re-circumscription of a misunderstood group of Orthotrichaceae that diversified in North America. (31st March 2020) - Lara, Francisco; Draper, Isabel; Flagmeier, Maren; Calleja, Juan Antonio; Mazimpaka, Vicente; Garilleti, Ricardo
Abstract: Orthotrichum lyellii was described in 1878 based on the crisped leaves with plane margins on its elongated and branched stems, and on the presence of brood-bodies. In Europe, these characters remain constant, but in North America several similar forms lacking propagules have been described either at the specific or infraspecific level. These were all reduced to synonyms of O. lyellii . In 2015, Orthotrichum was divided, and O. lyellii was transferred to Pulvigera, a genus thus far considered to be monospecific. In this study, the variability of P. lyellii is analysed in an integrative taxonomic framework. Morphological studies on > 200 specimens, including the nomenclatural types of the taxa previously described, were combined with biogeographical and ecological evidence and with a phylogenetic reconstruction of 39 terminals based on five molecular loci. All the sources of evidence suggest the existence of four different taxa in North America, one also present on the Marquesas Islands. The study of type materials led to their identification as P. lyellii and three other taxa previously described from North America, Orthotrichum papillosum, O. lyellii var. howei and O. pringlei . These taxa differ from each other in taxonomically significant morphological characters of the gametophyte and sporophyte. The morphological diversity has led us to reinterpret Pulvigera, and to amend its description. Nomenclatural changes for the reinstated taxa are proposed, and full descriptions and an identification key for Pulvigera spp. in North America are provided.